Vers une éducation à la biodiversité : prise en compte des savoirs, de l’affectivité et des comportements - Serge Franc; Christian Reynaud; Abdelkrim Hasni (Éducation et Socialisation)
From a global perspective, issues related to biodiversity have appeared in the collective awareness for over forty years. In France, biodiversity education has emerged as a priority linked with the degradation of biodiversity. The biodiversity education in primary school is attached to both the scientific topics and sustainable development. The expected learning follows two basic dimensions : bio-ecological knowledges and behaviors related to the expected knowledges. However, numerous studies show the significance of affective dimension in learning, especially regarding the emotional relationship with the objects of study. In the education context, a definition of biodiversity education is proposed, based on three dimensions related to learning : knowledge, emotions and behaviors.